Antiphospholipid syndrome presenting as acute mesenteric venous thrombosis involving a variant inferior mesenteric vein and successful treatment with rivaroxaban. (26th March 2018) - Singh, Kevin; Khan, Gulam
Abstract : Acute mesenteric venous thrombosis (MVT) is the rarest cause of acute mesenteric ischaemia, so thrombosis of a variant inferior mesenteric vein (IMV) is especially uncommon in the setting of antiphospholipid syndrome (APS). Here, we present such a case of seronegative APS initially manifesting as an anomalous IMV thrombosis in a 76-year-old woman. Although guidelines support anticoagulation with vitamin K antagonists in these patients, we anticoagulated with rivaroxaban (a direct oral anticoagulant (DOAC)) due to patient preference, which resulted in complete clinical and endoscopic resolution. IMV thrombosis is a rare form of MVT, only two case reports describe successful anticoagulation with DOACs in the setting of MVT and none report APS as an underlying aetiology. Therefore, this case provides the opportunity to review the pathophysiology of MVT, APS and their medical management including current trends in anticoagulation.